Physical Activity and Survival among Long-term Cancer Survivor and Non-Cancer Cohorts - Gunnell, Anthony S.; Joyce, Sarah; Tomlin, Stephania; Taaffe, Dennis R.; Cormie, Prue; Newton, Robert U.; Joseph, David; Spry, Nigel; Einarsdóttir, Kristjana; Galvão, Daniel A. (Frontiers in Public Health, 2017)
Evidence suggests physical activity improves prognosis following cancer diagnosis; however evidence regarding prognosis in long-term survivors of cancer is scarce. We assessed physical activity in 1,589 cancer survivors at an average 8.8 years following their initial diagnosis and calculated their future mortality risk following physical activity assessment. We also selected a cancer-free cohort of 3,145 age, sex and survey-year group-matched cancer-free individuals from the same source population for comparison purposes. Risks for cancer-specific mortality and all-cause mortality in relation to physical activity levels were estimated using Cox regression proportional hazard regression analyses within the cancer and non-cancer cohorts. Physical activity levels of 360+ mins per week were inversely associated with cancer-specific mortality in long-term cancer survivors (HR = 0.30 [95% CI 0.13-0.70]) and participants without prior cancer (HR = 0.16 [95% CI 0.05-0.56]), compared with no reported physical activity. Physical activity levels of 150-359 mins and 360+ mins were inversely associated with all-cause mortality in long-term cancer survivors (150-359 mins; HR = 0.55 [95% CI 0.31-0.97], 360+ mins; HR = 0.41 [95% CI 0.21-0.79]) and those without prior cancer (150-359 mins; HR = 0.52 [95% CI 0.32-0.86], 360+ mins; HR = 0.50 [95% CI 0.29-0.88]). These results suggest that meeting exercise guidelines of 150 mins of physical activity per week were associated with reduced all-cause mortality in both long-term cancer surviving and cancer-free cohorts. Exceeding exercise oncology guidelines (360+ min per week) may provide additional protection in terms of cancer-specific death.